GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 175548 species occurrences available in GBIF matching the query: TaxonKey: Salmo trutta Linnaeus, 1758. The dataset includes 175548 records from 177 constituent datasets: 2 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 99 records from Fishes in MZNA-VERT: ecological assessment of the Aragon river in Sangüesa (Spain). 24 records from International Barcode of Life project (iBOL). 3298 records from Fishes in MZNA-VERT: freshwater populations in the Erro river (Spain). PhD Project, Pedro Leunda.. 1 records from Collection du Musée d'Histoire Naturelle de Nice. 1560 records from Biologiezentrum Linz. 1 records from European Molecular Biology Laboratory Australian Mirror. 30 records from Countryside Council for Wales - Bullhead Survey Data in Wales. 1 records from Die Bachspezies 2008/2009. 15 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 2 records from Fish Collection of Hokkaido University. 1392 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 10 records from National System of Protected Areas in Poland - Animals. 31 records from Geographically tagged INSDC sequences. 15 records from Tasmanian Museum and Art Gallery provider for OZCAM. 47 records from Museum of Comparative Zoology, Harvard University. 3 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Unassessed data. 5 records from Biological Reference Collections ICM CSIC. 3 records from CSUC Vertebrate Collection. 5389 records from Atlas of Danish Fishes. 26 records from UAIC Ichthyological Collection. 2 records from Colección de peces y macroinvertebrados del Museo de Historia Natural de la Pontificia Universidad Javeriana. 114 records from The Fish Collection. 5 records from National Trust for Scotland Species Records. 456 records from Øvre Heimdalsvatn, Radiocaesium (Cs-137) monitored annually in brown trout (Salmo trutta). 272 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 100 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 3361 records from Inventaire National du Patrimoine Naturel : Atlas des poissons d'eau douce de France métropolitaine (2011). 1 records from Bay of Fundy Species List (OBIS Canada). 15 records from Collection Ichthyologie - SNSD. 1 records from Anymals+plants - Citizen Science Data. 406 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 16 records from LACM Vertebrate Collection. 18 records from The Fish Collection at the Zoologische Staatssammlung München. 27 records from ArtenFinder. 64 records from Australian Museum provider for OZCAM. 2199 records from Artdata. 93 records from BRERC species records recorded over 15 years ago. 1 records from UAFMC Fish. 204 records from Freshwater fishes of the Western Balkans. 5 records from Data collected on scitizen science web portal www.ornitho.cat. 11 records from Countryside Council for Wales - Lamprey Survey Data. 3673 records from Gillnet test fishing and radiocaesium (Cs-137) of brown trout (Salmo trutta) and Arctic char (Salvelinus aplinus) 2008 and 2009 from 20 Central Scandinavian lakes: Occurrences. 10 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 1 records from Staffordshire Ecological Record - SER Species-based Surveys. 21444 records from SLU Aqua Institute of Freshwater Research Swedish Electrofishing Registry - SERS. 130 records from Fish collection, Natural History Museum, University of Oslo. 3 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 4 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 2 records from Biodiversity records from Ireland - general. 9 records from SIO Marine Vertebrate Collection. 21 records from Collection Pisces SMF. 2 records from Merseyside BioBank (unverified). 11 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 25 records from Waarnemingen.be - Fish occurrences in Flanders and the Brussels Capital Region, Belgium. 22 records from AUM Fish Collection. 199 records from Ichthyology Collection - Royal Ontario Museum. 5 records from Fishes in MZNA-VERT: distribution of freshwater blenny in the Segre and Susia rivers (Spain). 2 records from University of California Museum of Paleontology. 2 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 379 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 40 records from Occurrence records of southern African aquatic biodiversity. 1 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 1 records from TNHC Ichthyology Collection. 461 records from Natural History Museum (London) Collection Specimens. 10 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 349 records from Monitoring data from the federal state Hesse (Germany). 8 records from ISM Ichthyology Collection. 5 records from iziko South African Museum - Fish Collection (AfrOBIS). 1 records from Individual Sightings. 5 records from Atlantic Reference Centre (OBIS Canada). 2 records from Staffordshire Ecological Record - SER Site-based Surveys. 27 records from Oregon State Ichthyology Collection. 2 records from CSIRO Ichthyology provider for OZCAM. 114 records from CUMV Fish Collection (Arctos). 15148 records from Ims fish tag database. 2 records from LSUMZ (LSU MNS) Fishes Collection. 289 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 3 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 774 records from Monitoring data from the federal state Saxony (Germany). 126 records from Arctic Species Trend Index (ASTI) : Freshwater. 6 records from Plan de vertebrados de la Patagonia. 4002 records from Fishes in MZNA-VERT: freshwater communities in the Larraun river (Spain). PhD project, Javier Oscoz & Master project, A. Cos.. 5 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 4 records from Wetland Inventory (NV). 3 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 71 records from HMAP-History pf Marine Animal Populations (CoML). 6 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 1 records from Gunma Museum of Natural History, Fish Specimen. 96 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 5 records from Freshwater Fish Specimens of Lake Biwa Museum. 17 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 20 records from Données ONF Faune-Flore-FOnge. 8 records from UCM Fish Collection (Arctos). 1431 records from Inventario Español de Especies Terrestres (MAGRAMA). 3 records from Coastal and marine species. 524 records from Fishes in MZNA-VERT: interactions between signal crayfish and fish communities. PhD project, Iván Vedia. 40 records from HBRG Vertebrates (not Badger) Dataset. 45760 records from NINA Vanndata fisk. 7 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 2 records from National Museum of Natural Science. 87 records from Fishbase. 12 records from UWFC Ichthyology Collection. 193 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 28 records from VIS - Reference freshwater monitoring in Flanders, Belgium (post 2013). 1 records from Seasearch Marine Surveys in Scotland. 1 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 23 records from Field Museum of Natural History (Zoology) Fish Collection. 792 records from Fishes in MZNA-VERT: populations affected by the Itoiz dam in the Irati river (Spain).. 339 records from Lund Museum of Zoology (MZLU). 1 records from Countryside Council for Wales - Shad Monitoring data. 10631 records from National fish tag database. 3 records from Fish Specimens. 2 records from Local BioBlitz Challenge 2013. 1 records from Fish Specimens of Museum of Tokushima Prefectural Museum, Japan. 1 records from Northern Territory Museum and Art Gallery provider for OZCAM. 123 records from NCSM Fishes Collection. 35 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 81 records from Museum Victoria provider for OZCAM. 13 records from Queen Victoria Museum Art Gallery provider for OZCAM. 415 records from NRM-Fishes. 225 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 1 records from E39 Lyngdal - Ålgård. 18 records from Fish specimens of Fisheries Research Laboratory Mie University. 4 records from Western Australian Museum provider for OZCAM. 4106 records from Norwegian Biodiversity Information Centre - Other datasets. 6 records from Image Database of Fishes in the Kanagawa Prefectural Museum of Natural History. 157 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 2970 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 33 records from BioFokus. 1 records from Priest Pot species list, Cumbria, Britain. 6 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 1 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 1139 records from Talvik fish tag database. 56 records from Ohio State University Fish Division (OSUM). 39 records from UF FLMNH Ichthyology. 21 records from Canadian Museum of Nature - Fish Collection (OBIS Canada). 6 records from Fish collection of National Museum of Nature and Science. 55 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 6 records from VIS - Fishes in inland waters in Flanders, Belgium. 4923 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 10 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 18 records from FHSM Fish Collection. 57 records from Ichthyology. 738 records from Norwegian Species Observation Service. 17 records from Biological and palaeontological collection and observation data MNHNL. 12 records from South Australian Museum Australia provider for OZCAM. 16 records from MSUM Ichthyology and Herpetology Collections. 1 records from Queensland Museum provider for OZCAM. 20 records from Données ONF Faune-Flore-Fonge. 29957 records from USGS Nonindigenous Aquatic Species database. 325 records from naturgucker. 1 records from Natural History Museum Rotterdam (NL) - Chordata collection. 108 records from iNaturalist Research-grade Observations. 1 records from Collection Paleoanthropology SMF. 4 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 1 records from The reptiles, amphibians and fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 14 records from Ireland's BioBlitz. 230 records from Limnodata. 207 records from NMNH Extant Specimen and Observation Records. 371 records from Fishes in MZNA-VERT: foraging ecology of the kingfisher. PhD project, Antonio Vilches. 20 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ichthyology National Collection (MACNIct). 24 records from Canadian Museum of Nature Fish Collection. 6 records from Ghent University - Zoology Museum - Vertebrate collection. 794 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 13 records from Naturalis Biodiversity Center (NL) - Pisces. 21 records from Collection Anatomie Histologie - SMF. 41 records from BRERC species records within last 15 years. 39 records from CAS Ichthyology (ICH). 8 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 39 records from Zoology (Museum of Evolution - Uppsala). 1 records from Akita Prefectural Museum＋Actinopterygius Specimens of Akita Prefectural Museum. 5 records from KUBI Ichthyology Collection. 8 records from Diveboard - Scuba diving citizen science observations. 1 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 1216 records from Fishes in MZNA-VERT: baseline freshwater sampling campaigns. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences